Advantages and possible hazards of incorporating zinc oxide nanoparticles into broilers' diets - Mahmoud, Usama T.; Seven, Ismail; Iflazoglu Mutlu, Seda; Cicek, Miray Sila; Tatli Seven, Pinar (Springer, 2025)
Zinc oxide nanoparticles (ZONPs) are increasingly regarded as a promising alternative to conventional zinc sources in broilers nutrition due to their superior bioavailability and multiple functional benefits. This review reported the role of ZONPs in enhancing broilers' health and performance, including improvements in growth rate, behavioral responses, meat quality, physiological functions, and biochemical markers, as well as their application to control coccidiosis, necrotic enteritis and footpad dermatitis. Their strong antimicrobial properties against key broiler pathogens such as Salmonella and Escherichia coli (E.coli) also improve gut health and food safety. Moreover, the efficient absorption of ZONPs leads to reduced zinc excretion, thus lowering the environmental burden commonly associated with traditional zinc supplementation. Despite these advantages, the potential risks of ZONPs should not be overlooked. Factors such as nanoparticle size, concentration, and duration of exposure influence their safety profile. While several studies report no significant organ toxicity, concerns remain regarding possible long-term effects on vital organs including the liver, kidneys, and reproductive system. Additionally, inconsistent findings and a lack of standardized safety assessments require more comprehensive research. This review provided a balanced overview of ZONPs in broiler feed, highlighting their promising benefits and associated risks.
Keywords: Zinc oxide nanoparticles; Broilers; Growth performance; Behavior and welfare; Meat quality; Physiological functions